Determination of the time constant of measuring transducers - Zakharov, I. P.; Neyezhmakov, P. (Zakharov I. Determination of the time constant of measuring transducers / I. Zakharov, P. Neyezhmakov // Measurement: sparking tomorrow’s smart revolution XXIII IMEKO World Congress “ August 30 September 3, 2021, Yokohama, Japan, 2021)
The methods for the experimental determination of the time constant of measuring transducers are described. The method is based on determining the parameters of the steady-state response of the measuring transducer using a periodic sequence of rectangular pulses of known time pulse and repetition period as an input signal. Expressions for determining the time constant for various response parameters: maximum, minimum, average, and average rectified values are given. The evaluation of the measurement uncertainty for each of the obtained expressions is made. The proposed method has high accuracy and low labour intensity in comparison with the known graph-analytical methods.
Keywords: time constant; measuring transducers; rectangular pulses